One-step pickling-activation before magnesium alloy plating - 王新娟 余刚 欧阳越军 何晓梅 张俊 叶立元 (Transactions of Nonferrous Metals Society of China, 2009)
A one-step pickling-activation process was proposed as an environmental friendly pretreatment method in phosphate-permanganate solution before electroplating on magnesium alloys. The effects of pickling-activation on qualities of coating were assessed by adhesion and porosity testing of copper plating. The interfacial reactions between specimen and solution were analyzed with SEM, EDX and XRD. The results show that the developed process of pickling-activation can equalize the potentials on substrate surface. The compacted zinc film can be obtained by zinc immersion after treating magnesium alloy in the pH 4-6 phosphate-permanganate solution for 3-5 min. The adhesion and corrosion resistance of copper plating are enhanced. The one-step pickling-activation can replace the existing two-step process of acid pickling and activation which contains a great deal of chromium and fluorine. The procedure of surface pretreatment is simplified and the production environment is improved.